Penerapan Sistem Informasi Berbasis Web Untuk Pengajuan Judul Skripsi Mahasiswa Sebagai Upaya Peningkatan Efesiensi Waktu - Rahmad Dinata; Indriaturrahmi; Edy Haryanto (Infotek: Jurnal Informatika dan Teknologi, 2025)
This research aims to design an online-based thesis title submission information system using Rapid Application Development (RAD). This system is designed to facilitate students who previously submitted thesis titles manually. The research method used is a quantitative approach by conducting observations, interviews, and questionnaires. The development stages include Requirement Planning, User Design, Development, and Cutover. Results In the research and development of this thesis title submission information system, the main objectives have been achieved well, namely being able to minimize time in the submission process and there is user satisfaction with this system because it has helped to do the submission process online. This system is designed to simplify and speed up the process of submitting, verifying, and determining a supervisor, which was previously done manually and took longer. By using PHP technology as a programming language and MySQL as a database system, this system successfully automates various administrative processes involved in managing thesis titles